PENOKOHAN PADA IKLAN LAYANAN MASYARAKAT PEKAN IMUNISASI NASIONAL - Supratman DP., Deny (Jurusan Seni Rupa STSI Bandung, 2013)
Public Service Advertisement is one way to persuade the society to understand, acknowledge, and give awarness on how they could so that society could position themselves from gething stuck with wrong messages on any advertisement issues that come within. One of the issues is Weekly National Immunization. The achievment of this program is one simultaneoust responsibility from every elements in the society. Whithout any of these colaboration from the people, this program won’t reachany great succes. This accomplishment was done by persuading the market through Public Service Advertisements that were designed with thoughtful scenarios and criterias of public figures.Keywords: Public Service Advertisements, Public Figures, Television, Visual